Editorial - De Marchi Pereira de Souza, Alice; Mattos, Amana; Lúcia Tinoco Ponciano, Edna; Santos Bispo, Fábio; Degani-Carneiro, Filipe; de Garay Hernández, Jimena; Cristina de Toledo Quadros, Laura; Vinicius Brunhari, Marcos; Albuquerque Hayasida, Nazaré; Lorena Quitério, Patrícia; et al. (Estudos e Pesquisas em Psicologia, 2023)
Alice De Marchi Pereira de Souza, Amana Mattos, Edna Lúcia Tinoco Ponciano, Fábio Santos Bispo, Filipe Degani-Carneiro, Jimena de Garay Hernández, Laura Cristina de Toledo Quadros, Marcos Vinicius Brunhari, Nazaré Albuquerque Hayasida, Patrícia Lorena Quitério, Rebeca Valadão Bussinger, Rodolfo Rodrigues de Souza, Rosana Lazaro Rapizo, Sabrina Dal Ongaro Savegnago, Vitor Castro Gomes